2016
DOI: 10.2298/tsci151203080g
|View full text |Cite
|
Sign up to set email alerts
|

Campus and community micro grids integration of building integrated photovoltaic renewable energy sources: Case study of Split 3 area, Croatia - part A

Abstract: Micro grids interconnect loads and distributed energy resources as a single controllable entity. New installations of renewable energy sources in urban areas, such as building integrated photovoltaic, provide opportunities to increase energy independence and diversify energy sources in the energy system. This paper explores the integration of renewable energy sources into two case study communities in an urban agglomeration to provide optimal conditions to meet a share of the electrical loads. Energy planning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Their study showed that social norms, trust, environmental concern and community identity were important determinants for successful local energy projects. Several authors have published studies on technologies that improve EE and renewable energy sources [13][14][15][16][17]. Schneider et al [18] claim that proper planning of systems with high penetration of intermittent renewable energy sources is the most important segment of future energy production development.…”
Section: Introductionmentioning
confidence: 99%
“…Their study showed that social norms, trust, environmental concern and community identity were important determinants for successful local energy projects. Several authors have published studies on technologies that improve EE and renewable energy sources [13][14][15][16][17]. Schneider et al [18] claim that proper planning of systems with high penetration of intermittent renewable energy sources is the most important segment of future energy production development.…”
Section: Introductionmentioning
confidence: 99%
“…The community solar microgrid establishment resulted in cost savings between $692 and $180,000 annually for the customers in the city of Boston (Morgan et al, 2016). A campus community solar microgrid study done by (Gašparović et al, 2016) investigated two microgrid community cases in the University of Split (Croatia) to identify optimum scenarios for the economic share of electrical loads in the settlement. The results from the study revealed that electricity purchases from the national electricity grid were offset by 17% through the campus microgrid system.…”
Section: Power-sharingmentioning
confidence: 99%
“…In the literature about BIPV, there are few investigations that combine BIPV with smart grids. In this field, additional studies are as follows: Mühlbauer (2017), Wang et al (2015), Gašparović et al (2016), project REMOURBAN. Another example is the study by Wang et al (2016a).…”
Section: Bipv and Bipvt With Battery Storage: Non-concentrating And Concentrating Systemsmentioning
confidence: 99%